Pulsatile Intravascular Lithotripsy for Heavily Calcified Femoropopliteal Arterial Disease: First-in-Human Results from the POWER PAD I Feasibility Study - Bibombe Patrice Mwipatayi; Bernardette Jingfei Lee; Davina Daudu; Nelson Encarnación Santana; Alexandra Lansky; Robert S. Chisena; Hitinder S. Gurm; Robert Traficante; Jon C. George (Journal of Clinical Medicine, 2026)
Background/Objectives: Severe arterial calcification remains a major challenge during femoropopliteal endovascular intervention, limiting luminal gain and increasing the risk of vessel-wall injury, restenosis, and bailout stenting. Pulsatile intravascular lithotripsy (PIVL) is a novel calcium-modification technology that converts pneumatic pulses into short-duration hydraulic pressure waves delivered through a non-compliant balloon. POWER PAD I evaluated the first-in-human feasibility, safety, and procedural performance of PIVL in calcified femoropopliteal arterial disease. Methods: POWER PAD I was a prospective, single-arm, two-center feasibility study. Adults with Rutherford category 2–4 symptomatic peripheral arterial disease and moderately or severely calcified superficial femoral or popliteal lesions were treated with PIVL, followed by adjunctive therapy when clinically indicated. Angiographic and duplex ultrasound outcomes were assessed by an independent core laboratory, and adverse events were adjudicated by an independent clinical events committee. Results: Nine patients underwent treatment of 20 lesions. Mean age was 76.2 ± 12.6 years, 19 lesions were severely calcified, and five lesions were chronic total occlusions. Patient-level device and procedural success were each achieved in 8 of 9 patients; technical success was achieved in all patients. Mean diameter stenosis decreased from 76.5 ± 18.0% before treatment to 28.1 ± 6.9% after PIVL-containing lesion preparation and before adjunctive drug-coated-balloon angioplasty, and to 20.6 ± 5.8% after adjunctive therapy. Mean minimal luminal diameter increased from 1.3 ± 1.0 mm to 3.8 ± 0.5 mm after PIVL-containing lesion preparation and to 4.3 ± 0.6 mm at final angiography. No perforation, distal embolization, thrombus, abrupt closure, no-reflow, bailout stenting, or grade D or higher dissection occurred. Freedom from clinically driven target-lesion revascularization was 100% at 30 days and 6 months. Conclusions: PIVL-containing lesion preparation was feasible in heavily calcified superficial femoral and popliteal lesions and was associated with substantial acute luminal gain before adjunctive DCB therapy and no severe angiographic complications. Favorable 6-month clinical and patency outcomes were observed after the combined treatment strategy of PIVL vessel preparation and adjunctive DCB therapy; therefore, longer-term outcomes cannot be attributed to PIVL alone. Larger controlled studies are warranted.